The role of comparative victim beliefs in predicting support for hostile versus prosocial intergroup outcomes. (5th May 2021) - Vollhardt, Johanna Ray; Cohrs, J. Christopher; Szabó, Zsolt Péter; Winiewski, Mikołaj; Twali, Michelle S.; Hadjiandreou, Eliana; McNeill, Andrew
Abstract: Collective memories of historical ingroup victimization can be linked to prosocial or hostile intergroup outcomes. We hypothesize that such discrepant responses are predicted by different construals of the ingroup's victimization in relation to other groups (i.e., comparative victim beliefs). Using improved measures of inclusive and exclusive victim beliefs, with a global or regional reference group, multigroup structural equation modeling showed across four different groups (Armenian Americans [ N  = 265], Jewish Americans [ N  = 297], Hungarians [ N  = 301], Poles [ N  = 468]) that inclusive victim beliefs predict prosocial, conciliatory attitudes, while exclusive victim beliefs predict hostile attitudes towards historical perpetrator groups and (in the Polish and Hungarian samples) religious and ethnic outgroups targeted in the present. Moreover, comparative victim beliefs mediated effects of more general psychological orientations (ingroup superiority, universal orientation, perspective‐taking) on intergroup outcomes. These findings suggest the importance of considering distinct collective victim beliefs, and different contexts in research on collective victimhood.